Aftereffects and Deactivation of Completed Prospective Memory Intentions: A Systematic Review - Möschl, Marcus (Psychol Bull, 2019)
Prospective memory, the ability to perform an intended action in the future, is an essential aspect of goal-directed behavior. Intentions influence our behavior and shape the way we process and interact with our environment. One important question for research on prospective memory and goal-directed behavior is whether this influence stops after the intention has been completed successfully. Are intention representations deactivated from memory after their completion? And if so, how? Here we systematically review twenty years of research on intention deactivation and so-called aftereffects of completed intentions across different research fields in order to offer an integrative perspective on this topic. We first introduce the currently dominant accounts of aftereffects (inhibition vs. retrieval) and illustrate the paradigms, findings and interpretations that these accounts developed from. We then review the evidence for each account based on the extant research in these paradigms. While early studies proposed a rapid deactivation or even inhibition of completed intentions, more recent studies mostly suggested that intentions continue to be retrieved even after completion and interfere with subsequent performance. Although these accounts of aftereffects seem mutually exclusive, we will show that they might be two sides of the same coin. That is, intention deactivation and the occurrence of aftereffects are modulated by a multitude of factors that either foster a rapid deactivation or lead to continued retrieval of completed intentions. Lastly, we outline future directions and novel experimental procedures for research on mechanisms and modulators of intention deactivation and discuss practical implications of our findings.